Biscuit Purchasing Procedure at PT. Semestanustra Distrindo Branch Banjarmasin - Boy sapto suryo; Hikmah Ariani (Fakultas Ekonomi Universitas Indonesia Timur, 2022)
The research, entitled Biscuit Purchasing Procedure at PT. Semestanustra Distrindo in Banjarmasin aims to obtain an overview of